2019
DOI: 10.1177/0894439318813586
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Versus Digitally Recorded: Measuring Political Activity on Facebook

Abstract: Facebook has been credited with expanding political activity by simultaneously lowering barriers to participation and creating new ways to engage. However, many of these findings rely on subjects’ abilities to accurately report their Facebook use and political activity on the platform. This study combines survey responses and digital trace data from 828 American adults to determine whether subjects over- or underreport a range of political activities on Facebook, including whether they like political pages or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 40 publications
1
29
0
2
Order By: Relevance
“…The most robust results across validation studies and the most problematic finding for the field of political communication are that political interest is both correlated with misreporting (Guess et al, 2018;Haenschen, 2019;Vraga & Tully, 2018) and, as is well-known, with factors like voting or political knowledge. It is also noteworthy that the relationship between misreporting and political variables all come from the United States, an increasingly polarized political and media system.…”
Section: Linking Surveys and Digital Trace Data: Ways Of Linking And mentioning
confidence: 94%
See 2 more Smart Citations
“…The most robust results across validation studies and the most problematic finding for the field of political communication are that political interest is both correlated with misreporting (Guess et al, 2018;Haenschen, 2019;Vraga & Tully, 2018) and, as is well-known, with factors like voting or political knowledge. It is also noteworthy that the relationship between misreporting and political variables all come from the United States, an increasingly polarized political and media system.…”
Section: Linking Surveys and Digital Trace Data: Ways Of Linking And mentioning
confidence: 94%
“…Further studies should investigate whether political considerations affect survey responses on (online) behavior in other contexts as well. These studies have also shown ways to improve survey items by testing various types of self-report items against each other (Guess, 2015;Guess et al, 2018;Haenschen, 2019).…”
Section: Linking Surveys and Digital Trace Data: Ways Of Linking And mentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional approach to measuring media use has been to ask respondents post hoc about their use. However, this kind of measurement has long been suspected of generating systematic error, as people tend to overestimate their exposure times (Haenschen, 2019;Price & Zaller, 1993;Prior, 2009;Scharkow, 2016). While previous research has shown that, for example, open-ended questions reduce such overreporting (Guess, 2015), post-hoc surveys provide no reliable way to capture individually encountered context.…”
Section: Surveysmentioning
confidence: 99%
“…Debates on Facebook were also heated during elections in various countries, including the USA Presidential Elections since 2008 (see Williams and Gulati 2008;Robertson et al 2008;Fernandes et al 2010;Carlisle and Patton 2013;Pennington et al 2015;Lin 2017; Apuke and Apollos 2017). Public and politicians' participation in political discourse on Facebook has also been the subject of several studies, including ones on comments on political posts and issues (see Chen and Sali 2010;Clarke and Steekamp 2014;Vraga et al 2015;Heo et al 2016;Haenschen 2019). Reactions to Facebook extremist political comments (Almoqbel et al 2019) and hostile media bias on social media expressed in users' comments (Gearheart et al 2020) were also the subjects of some recent studies.…”
Section: Introductionmentioning
confidence: 99%